2018
DOI: 10.1016/j.eururo.2018.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Focal Therapy in Primary Localised Prostate Cancer : The European Association of Urology Position in 2018

Abstract: Focal therapy of prostate cancer is the targeted destruction of cancer within a specific part of the prostate gland, sparing the rest of the prostate and nearby tissue. This procedure could potentially reduce side effects when compared with established standard treatments, such as surgery or radiotherapy, which treat the entire prostate. Studies show that for most men with low-risk cancer, active surveillance is the preferred treatment option. However, the available data regarding all forms of focal therapy ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
98
0
9

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 144 publications
(114 citation statements)
references
References 66 publications
2
98
0
9
Order By: Relevance
“…High sensitivity at the voxel level is important for focal therapy planning. 29 We have shown that 10-12 mm distance (corresponding to the Hausdorff distance) of prospectively delineated lesions led to sensitivity approaching 95% in the majority of IMPROD bpMRI-detected lesions. In order to achieve close to 100% sensitivity, increasing IMPROD bpMRI manual declinations by~10-12 mm in all directions was necessary ( Table 3).…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…High sensitivity at the voxel level is important for focal therapy planning. 29 We have shown that 10-12 mm distance (corresponding to the Hausdorff distance) of prospectively delineated lesions led to sensitivity approaching 95% in the majority of IMPROD bpMRI-detected lesions. In order to achieve close to 100% sensitivity, increasing IMPROD bpMRI manual declinations by~10-12 mm in all directions was necessary ( Table 3).…”
Section: Discussionmentioning
confidence: 80%
“…In the current study, high sensitivity at the ROI level (within the whole prostate) was achieved, in contrast to the sensitivity at the voxel level, which was limited. High sensitivity at the voxel level is important for focal therapy planning . We have shown that ~10–12 mm distance (corresponding to the Hausdorff distance) of prospectively delineated lesions led to sensitivity approaching 95% in the majority of IMPROD bpMRI‐detected lesions.…”
Section: Discussionmentioning
confidence: 97%
“…While IRE is a promising focal ablative technique with good short-term oncological results and minimal morbidity, it should still be considered an investigational treatment performed only as part of prospective clinical registry studies or randomised trials until more long-term data are available [43,44].…”
Section: Future Perspectives and Conclusionmentioning
confidence: 99%
“…Most mpMRIs were performed with a pelvic phased-array coil without an endorectal coil. Systematic TRUS biopsies of the prostate (12 cores according to a standard scheme: two per sextant), one biopsy of the proximal part of each seminal vesicle, and at least two biopsies in each mpMRI target, were taken [17]. Initial metastatic evaluations included bone scan and thoracoabdomino-pelvic CT.…”
Section: Study Populationmentioning
confidence: 99%